Pre‐ and probiotics for allergy prevention: time to revisit recommendations?. Issue 12 (28th November 2016) - Forsberg, A.; West, C. E.; Prescott, S. L.; Jenmalm, M. C.
Summary: Reduced intensity and diversity of microbial exposure is considered a major factor driving abnormal postnatal immune maturation and increasing allergy prevalence, particularly in more affluent regions. Quantitatively, the largest important source of early immune‐microbial interaction, the gut microbiota, is of particular interest in this context, with variations in composition and diversity in the first months of life associated with subsequent allergy development. Attempting to restore the health consequences of the 'dysbiotic drift' in modern society, interventions modulating gut microbiota for allergy prevention have been evaluated in several randomized placebo‐controlled trials. In this review, we provide an overview of these trials and discuss recommendations from international expert bodies regarding prebiotic, probiotic and synbiotic interventions. Recent guidelines from the World Allergy Organization recommend the use of probiotics for the primary prevention of eczema in pregnant and breastfeeding mothers of infants at high risk for developing allergy and in high‐risk infants. It is however stressed that these recommendations are conditional, based on very low‐quality evidence and great heterogeneity between studies, which also impedes specific and practical advice to consumers on the most effective regimens. We discuss how the choice of probiotic strains, timing and duration of administration can critically influence the outcome due to different effects on immune modulation and gut microbiota composition. Furthermore, we propose strategies to potentially improve allergy‐preventive effects and enable future evidence‐based implementation.